Industry Management Instruments in the First 10 Years of Economic Transformation in Poland (1989–1999) - Klimek, Dariusz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2019)
The aim of this article is the assessment of the effectiveness of economic and industrial policy instruments for the restructuring of Polish industry in the first 10 years of transformation. The first part contains the register of selected experiences and phenomena that contributed to the use of these instruments. In the second part of the article, the author gave a brief description of the instruments used at the time, such as: prices, taxes, tariffs and non-tariff solutions, settlement and court proceedings with creditors, government and industry restructuring programs, institutions supporting restructuring, financing of research works, subsidies, concessions, sureties and guarantees of the Treasury, government investments, protection of the market against imports, offset transactions. The author hypothesised that the low effectiveness of economic and industrial policy instruments was one of the reasons for the bankruptcy of a large part of Polish industry in the years 1989-1999. The third part presents the empirical research results on their effectiveness in the form of expert survey performed at the end of 2018. The basic conclusion from the conducted research confirms the hypothesis and is not optimistic. Despite the large number of instruments of economic and industrial policy existing at that time, their efficiency was poor. A number of important instruments were missing that could have a significant impact on changes and their effects on Polish industry in the first years of transformation.